ANALISIS HARGA POKOK PRODUKSI DAN HARGA POKOK PENJUALAN JAGUNG DI KECAMATAN SEKAMPUNG UDIK KABUPATEN LAMPUNG TIMUR - Fitri Solekhah; Wan Abbas Zakaria; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2018)
This research is to find out determining production cost and selling cost of corn and the affect use of various kinds of seed corn in the determining production cost.  The research was conducted in July - August and used a survey method in Sidorejo Village, Sekampung Udik Subdistrict, East Lampung Regency. The samples of this research are 52 corn farmers selected randomly.  Analysis of data is conducted using the determining production cost, determining selling cost, and one way Anova.  Analysis of the cost of goods production used the margin profit of 15 percent. The results showed determining that production cost is Rp1,383.00/kg for Bisi-18, Rp1,379.28/kg for NK-33, Rp1,448.77/kg for Pioneer-27, and Rp1,359.52/kg for DK-95.  Determining selling cost with profit margin 15% for Bisi-18 is Rp1,590.45/kg, Rp1,586.18/kg for NK-33, Rp1,666.09/kg for Pioneer-27, and Rp1,560.00/kg for DK-95. The average price received by the farmers as much as Rp1,741.04/kg, It means that farmers have benefit from technicial efficiency of corn farming. The use of various kinds of seeds does not affect determining production cost. Key words: determining production cost, determining selling cost, technicial efficiency of corn